Holocene Environmental Evolution Response to the Human Activities and East Asian Summer Monsoon Variation in the Liangzhu Ancient City Complex, Eastern China - Zou, Chunhui; Mao, Longjiang; Shan, Siwei; Zhaocheng, Shuangping; Mo, Duowen (Frontiers in Marine Science, 2022)
The Liangzhu Ancient City Complex is located in a low-lying coastal delta area, and its environmental evolution would have had a significant impact on the human-environment interactions. In this study, element geochemistry and grain size of the sediment sequence from a dam section in Ganggongling (GGL) reveal crucial aspects of sedimentary dynamics, environmental evolution, human activities, and East Asian Summer Monsoon(EASM) variation in the Liangzhu area since 5500 a. Starting from the middle-to-late Holocene, the GGL section shows an overall transition from warm humidity to cold-dry, which is consistent with the climate record dimension in southern China. Through comprehensive analysis of the sedimentary environment before and after the dam’s completion, it can be found that the Ganggongling dam has played a positive role in regulating mountain torrents and met the needs of production and domestic water, such as rice planting through water storage. Further applications on the multi-decadal to centennial time scale demonstrate that variations in solar activity may control the EASM intensity mainly in southern China, which is subject to ENSO intensity changes.